Association between adolescents' body mass index and excessive use of electronic media - Wafaa Abod; Khamees Bandar Obaid (Kashan University of Medical Sciences, 2023)
Background: High body mass index (BMI) is associated with many health risks. Studies on the effect of excessive use of electronic media (EM) on high BMI are inconsistent.Objectives: The purpose of this study was to investigate the relationship between excessive use of EM and BMI among adolescents.Methods: A cross-sectional study was conducted with 382 students from middle and secondary schools in Kerbala City, Iraq. Data were collected from October 10, 2022, to December 20, 2023. Data collection was performed using a two-part self-report instrument. The first part contained items on participants' characteristics (including BMI) and the second part was the Excessive Use of Electronic Media Questionnaire (EUEMQ). Data were analyzed using independent t-test, analysis of variance, and linear regression analysis.Results: The mean age of the students was 15.90 ± 1.36 years, and most of them were middle school students (62.6%). Approximately half of the students had a normal BMI, while 22.2% were overweight or obese. Mean BMI differed significantly between males and females (21.02±5015 vs. 23.14±4.33, P< 0.001). The majority of students (47.4%) spent 2-5 hours on the Internet each day. Approximately 56.8% and 18.1% of the students reported moderate and severe EM use, respectively. The mean hours spent on the Internet and mean EM use did not differ significantly among students in different BMI categories. However, linear regression analysis showed that male gender (P < 0.001), number of hours spent online (P = 0.026), and excessive use of EM (P < 0.001) significantly influenced BMI.Conclusion: Excessive use of EM was found to increase the likelihood of being overweight in adolescents. Because of the health risks associated with high BMI, education and health authorities, and nurses, need to educate adolescents, about the health risks of excessive use of EM.